Guide to criminal procedure for California - Snipes, Jeffrey B. (Thomson Wadsworth, 2005)
Available for convenient bundling with any Wadsworth Criminal Procedure text or for purchase as a stand-alone item, this state-specific guide assists students in their exploration of California procedure laws and cases and features chapter introductions, overviews of codes and implications, and exercises for California-specific penal codes